Theory to practice: what teacher trainees did not expect from their practicum experience - Noordin, Nooreen; Abd Samad, Arshad; Mohamed Razali, Abu Bakar; Ismail, Lilliati; Md Rashid, Juridah (Universiti Sains Malaysia, 2019)
The teaching practicum plays an important role in the process of introducing pre-service teachers to the teaching profession which ultimately guides their professional growth. This paper explores and articulates an understanding of the experiences trainees go through during the short 12-week placement in schools. A study was carried out to get insights into the experiences and challenges they go through via the reflections written starting from week 1 until week 10. The trainees were asked to reflect on their experiences based on four categories: 1) teaching and learning, 2) relationship with the school administrator, 3) relationship with the mentor, and 4) relationship with the supervisor. A total of 25 teacher trainees’ reflections were analysed and key terms were coded and grouped according to the categories identified. The findings revealed that the teacher trainees’ experiences with regard to their teaching practicum were generally positive. However, there were also some inconsistencies found from their writings particularly with their expectations concerning their role in the school and their relationship with their mentors as well as supervisors. The kinds of challenges and unexpected experiences faced ranged from interpersonal to pedagogical issues. Some suggestions on improving the quality of the teaching practicum process within the program are discussed.